Estudio de factibilidad de una empresa dedicada a la producción y comercialización de tamales de chocho en la ciudad de Quito. - Peñafiel Catacta, Carlos Eduardo (2013)
This document presents technical and systematic way the feasibility study of creating a company dedicated to the production and merchandising of “tamales de chocho” in the Quito city. The project is divided into five chapters; the first chapter refers to external analysis as inflation, basic food basket, poverty, country risk, and the company's internal analysis by SWOT in order to establish strategies for the proper functioning of the company. The second chapter covers the market research, which shows the consumption of tamales in the Quito city with a demand of 11´466.672 units considering that each family consumes 26 units per year, and the company will have participation 5 %, growth of families in the city is 2.7% annually.